Museum Development and Cultural Representation : Developing the Kelabit Highlands Community Museum - Sweet, Jonathan; Kelly, Meghan; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Museum Development and Cultural Representation critically examines the development of a museum and cultural heritage centre in the indigenous Kelabit Highlands in Sarawak, Malaysia. Building on their direct involvement in the development of the project, the authors appraise the process in retrospect through a thematic analysis. Themes covered include the project s local and international contexts, community involvement and agency, the balance of tourism and authenticity, and the role of non-local partners. Through their analysis, the authors unpack the complexities of cultural representation and identity in heritage design practice, and investigates the relationship between capacity building and agency in cultural heritage management. Situating the project within international trends in museology, Museum Development and Cultural Representation offers a valuable case example of a heritage-making process in an indigenous community. It will be of interest to scholars and students studying cultural representation, as well as communities and museum professionals looking to develop similar projects.
A unique cultural museum -- Shaping Kelabit conservation processes in Southeast Asia. -- History, knowledge and the representation of identity. -- Museum development and tourism; identifying authenticity and representation -- Indigenous knowledge in community museum practice -- Shaping the discussion on conservation -- The development of the Kelabit Highlands Community Museum -- Detailed encounters -- Concluding remarks.
Includes bibliographical references and index.
Also available in print format.
Keywords: Kelabit (Southeast Asian people) -- Social conditions -- Exhibitions; Electronic books